P.A. Mbenzi and D.N. Iithete. English-Oshindonga Dictionary for Primary Schools - Beyer, Herman L. (Lexikos, 1997)
Review of P.A. Mbenzi and D.N. Iithete. English-Oshindonga Dictionary for Primary Schools